It's all about me-ow : a young cat's guide to the good life - Talbott, Hudson (New York : Nancy Paulsen Books, 2012)
A cat gives three kittens advice on how to charm, entertain, and communicate with their new human family.
School Library Journal starred, August 2012
Publisher's Weekly, August 2012
Kirkus Review, August 2012
2.5
K-3
Keywords: Cats -- Juvenile fiction; Cats -- Fiction; Humorous stories; Cats -- Fiction; Humorous fiction; Humorous fiction; Picture books for children